Public pastoral care approach in addressing tensions in marriages within Southern African churches and communities - Makumbini, Primrose; Magezi, Vhumani; Nanthambwe, Patrick (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2025)
Public pastoral care, as practised by churches and communities, can play a crucial role in helping African couples navigate the tensions that arise between African marriage traditions and Western cultural influences. For such care to be effective, it must be contextualised within the lived realities and public spaces of African societies. This article proposes a model of public pastoral care that is both ecclesial and communal in character, designed to support African marriages as they negotiate these cultural tensions. Drawing on the intersection between African marriage practices and the tensions currently affecting them, the article addresses the following questions: How can public pastoral care be conceptualised within African contexts? In what ways can it engage African public life? What are the major tensions influencing African marriages within these publics? And how can a contextualised framework of public pastoral care function as an intervention for couples experiencing such tensions? In response, the article first conceptualises public pastoral care within the African context, then explores its practice within African public, followed by an analysis of marital tensions, and finally presents a contextual pastoral framework aimed at strengthening marriages amid competing cultural expectations. Contribution: This article contributes by proposing a contextual model of public pastoral care that enables African couples to manage cultural tensions within marriage, thereby strengthening families and fostering healthier communities.